1986
DOI: 10.1111/j.1365-2265.1986.tb01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Circadian Rhythm of Melatonin in Diabetic Autonomic Neuropathy

Abstract: The circadian rhythm of melatonin secretion from the pineal body is entrained to the light-dark cycle and is controlled via sympathetic fibres originating from the superior cervical ganglia. We have therefore examined plasma melatonin profiles in diabetics with and without evidence of autonomic neuropathy and in normal matched controls. The physiological increase in nocturnal plasma melatonin concentration was not observed in diabetics neuropaths. There was no consistent pattern in the diabetics without neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 14 publications
5
30
0
Order By: Relevance
“…Although there was no significant difference in plasma melatonin between the lean and T2DM groups, this comparison is less meaningful than the comparison between weight-matched obese non-diabetic and T2DM groups, due to the effects of obesity per se described above. Reduced amplitude melatonin rhythms have been previously reported in T2DM patients with autonomic neuropathy [26], [27] and retinopathy [28]. A further study has reported a small decrease in serum melatonin across the 24-hour diurnal cycle in T2DM patients [29]; however, many of these individuals were extremely obese (mean BMI  = 44 for T2DM versus 34 for non-T2DM ) and there were no other participant details provided, making interpretation of the data extremely difficult.…”
Section: Discussionmentioning
confidence: 87%
“…Although there was no significant difference in plasma melatonin between the lean and T2DM groups, this comparison is less meaningful than the comparison between weight-matched obese non-diabetic and T2DM groups, due to the effects of obesity per se described above. Reduced amplitude melatonin rhythms have been previously reported in T2DM patients with autonomic neuropathy [26], [27] and retinopathy [28]. A further study has reported a small decrease in serum melatonin across the 24-hour diurnal cycle in T2DM patients [29]; however, many of these individuals were extremely obese (mean BMI  = 44 for T2DM versus 34 for non-T2DM ) and there were no other participant details provided, making interpretation of the data extremely difficult.…”
Section: Discussionmentioning
confidence: 87%
“…This antagonism is in line with the fact that, in man, the low insulin levels at night and high levels during the day coincide with elevated nocturnal melatonin concentrations and reduced levels during the day [37]. In addition, diabetic patients are largely devoid of a circadian melatonin rhythm [38,39]. Altogether, the cited findings clearly indicate that melatonin-insulin interactions, which are modulated and regulated by catecholamines, particularly norepinephrine [40–46], play an important role in glucose metabolism.…”
Section: Introduction Historical Aspectsmentioning
confidence: 76%
“…A further important aspect concerns the contrasting findings of impairments of insulin secretion by the overexpressed MT2 G allele and the observed reduced melatonin levels in patients with diabetes [110,[116][117][118][119][120]. The reduction in melatonin levels should presumably be considered as a primary change that is associated with the initiation and/or progression of the disease.…”
Section: Please Insert Table 2 About Herementioning
confidence: 99%